2004
DOI: 10.1002/ps.960
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility of metam sodium with halogenated fumigants

Abstract: Metam sodium (metam) is a widely used soil fumigant. Combined application of metam and other available fumigants is intended to produce synergic pesticidal effects for a broad spectrum of pest control in soil fumigation. This study aimed to test the compatibility of metam with the halogenated fumigants 1,3-dichloropropene (1,3-D), chloropicrin, methyl bromide, methyl iodide and propargyl bromide. Halogenated fumigants and metam were spiked simultaneously into organic solvents, water and moist soils, and metam-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Simultaneous application of metam‐sodium and halogenated fumigants (e.g. chloropicrin and 1,3‐D) was found to accelerate the degradation of the halogenated fumigants, reducing their availability in the soil 37, 38. The relatively high application rates in the present tests possibly masked this effect, or the transformation of chloropicrin and 1,3‐D occurs more rapidly in California than in Georgia soils.…”
Section: Discussionsupporting
confidence: 81%
“…Simultaneous application of metam‐sodium and halogenated fumigants (e.g. chloropicrin and 1,3‐D) was found to accelerate the degradation of the halogenated fumigants, reducing their availability in the soil 37, 38. The relatively high application rates in the present tests possibly masked this effect, or the transformation of chloropicrin and 1,3‐D occurs more rapidly in California than in Georgia soils.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have found that the simultaneous application of MNa and halogenated fumigants (e.g. Pic and 1,3‐D) was found to accelerate the degradation of the halogenated fumigants, reducing their availability in soil 36, 37. The present laboratory trials on the combined application of 1,3‐D + DZ did not indicate this type of degradation; however, the relatively high application rates in the present tests possibly masked the effect 4…”
Section: Discussioncontrasting
confidence: 66%
“…33,34 However, the combined application of DMDS plus DZ did not exhibit degradation according to the positive synergistic effects observed from the different rates tested in our laboratory. It has been reported that relatively high application rates may possibly mask degradation; 4 however, both high and low rates were tested in our laboratory studies.…”
Section: ■ Discussionmentioning
confidence: 47%